2017
DOI: 10.1177/1535370217700521
|View full text |Cite
|
Sign up to set email alerts
|

Heart-rate variability depression in porcine peritonitis-induced sepsis without organ failure

Abstract: Depression of heart-rate variability (HRV) in conditions of systemic inflammation has been shown in both patients and experimental animal models and HRV has been suggested as an early indicator of sepsis. The sensitivity of HRV-derived parameters to the severity of sepsis, however, remains unclear. In this study we modified the clinically relevant porcine model of peritonitis-induced sepsis in order to avoid the development of organ failure and to test the sensitivity of HRV to such non-severe conditions. In 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
(59 reference statements)
2
2
0
Order By: Relevance
“…In addition to this, the SDNN power is relatively low in all the animal groups as reported in other studies [ 28 ]. This gives a strong importance to the spectral variations observed during the endotoxemic aggression.…”
Section: Discussionsupporting
confidence: 70%
“…In addition to this, the SDNN power is relatively low in all the animal groups as reported in other studies [ 28 ]. This gives a strong importance to the spectral variations observed during the endotoxemic aggression.…”
Section: Discussionsupporting
confidence: 70%
“…In general, the vascular smooth muscle tone is a product of intensive crosstalk of local (humoral) regulatory mechanisms and of central regulatory mechanisms of the autonomic nervous system, dominantly the sympathetic branch. Analysis of heart rate variability, in agreement with our previous studies [14,26], revealed a shift of the sympathovagal balance toward sympathetic dominance (increase in LF component, decrease in HF component) in both groups to a similar extent. However, the increased sympathetic drive, in the group of septic shock even with further support of therapeutic administration of norepinephrine, did not override (peripheral) vasodilatory mechanism, and consequently, it did not prevent a marked reduction of the systemic vascular resistance.…”
Section: Discussionsupporting
confidence: 91%
“…In short, autologous feces (1 g/kg for inducing septic shock or 0.5 g/kg for inducing sepsis) were inoculated in the abdominal cavity after short cultivation (10 h, isotonic saline, 37 • C). The selection of doses was based on earlier studies of our group [11][12][13][14]. The high dose (1 g/kg) was sufficient in our experimental setting for the development of irreversible septic shock with sustained vasopressor support within 20-22 h. The low dose (0.5 g/kg) invariably did not induce septic shock within 24 h (no sustained vasopressor support, low plasma levels of lactate).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Interdisciplinary collaboration with bioengineering, statistics and mathematics can help to make more of the data acquired. For example, the extraction of heart rate variability or other detailed cardiovascular changes [103][104][105][106][107] can be generated from preclinical blood pressure or ECG waveforms and can be combined with inflammatory biomarkers, to build a more detailed picture of the physiological status of the animal. Reassuringly, such interdisciplinary analytical approaches have already led to the successful development of early alert systems in patients [108].…”
Section: Cardiovascular Monitoring Technologies That Support Refinementmentioning
confidence: 99%